Program Inovasi Desa (PRO-IDE) Mengintegrasikan Ekonomi Kreatif dan Pertanian Inovatif Dalam Pembangunan Kampung Wisata Edukasi Hijau di Kelurahan Bakung Jaya - Faradina Zevaya; Tri Suciana Situmorang; Elisa Elisa; Dini Syaharani; Julas Widiasari; Keke Aprianti; Shela Pirnanda (Masyarakat Berkarya : Jurnal Pengabdian dan Perubahan Sosial, 2024)
This research explains the Village Innovation Program (PRO-IDe) which aims to combine creative economy and innovative agriculture in the development of the Green Education Tourism Village in Bakung Jaya Village. This program utilizes local resources to empower communities through training and mentoring in sustainable agricultural practices as well as the development of creative products based on existing natural resources. In this way, it is hoped that people can improve their welfare, open new jobs, and attract tourists. In addition, this study also examines the social and economic impacts of the implementation of PRO-IDe as well as the challenges that arise in integrating these two sectors. The results of this study are expected to provide useful inputs for the development of policies and practices in other villages that have similar potential.